IMPROVING CHILDREN'S FINE MOTORCYCLE DEVELOPMENT THROUGH PLASTICINE MEDIA IN TK AISYIYAH BUSTANUL ATHFAL TEMPURAN TRIMURJO - Amirul Mukminin Al Anwari; Anis Fitriani; Aulia Rahma (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2021)
Every child is born with their own potential, children are small humans who have potential that must be developed. Children have certain characteristics that are unique and not the same as adults, they are always active, dynamic, enthusiastic and want to know what they see, feel and never stop exploring in learning. Media is a tool used to support the implementation of the learning process. Through the media can gain knowledge that can develop self-ability. Plasticine media is one of the construction media that is useful for children. plasticine consists of various colors that are liked by children. Based on the results of the study, it was shown that there were many children in TK Aisyiyah Bustanul Athfal Tempuran Trimurjo whose fine motor development had not developed very well. This study aims to improve children's fine motor development through plasticine media in TK Aisyiyah Bustanul Athfal Tempuran Trimurjo. This research method is Classroom Action Research (CAR). This research was conducted using two cycles and in each cycle three meetings were carried out. The subjects of this study were 16 Aisyiyah Bustanul Athfal Tempuran Trimurjo Kindergarten children, consisting of 9 boys and 7 girls. Methods of data collection is done through observation and documentation. The data analysis technique was carried out qualitatively. The improvement of fine motor development is said to be successful if 11 out of 16 children are able to achieve the criteria for Very Good Development (BSB) with a percentage of 69%. The results showed that the plasticine media could improve the fine motor development of children. Before the action was taken, no child had developed very well. After the action in the first cycle, the children's fine motor development increased by 4 children with a percentage of 25%, and in the second cycle it increased to 11 children with a percentage of 69% very well developed criteria (BSB). In the use of plasticine media, the teacher introduces how to form plasticine and print plasticine, then children can try to practice it, with their friends.